(3GdchGcH GdOQjI aj GdCUhd GdLaQjIs - (3Sdje GdMfajs
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ Sdje GdMfaj GdhGYX GdehUdj deG CfYe Gddg Ydi HJMUjd cJH GdeGOI hbQGJgG QZHJ aj eWGdYI GdcJH GdLaQjI s
(3BNQgG (B:s
(3hgPg bGYOI YXjeI GdfaY aGYed HgG JQTO Edi WQjb GdUhGH hEdjg GdeQLY hGdeBH hGddg CYde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQcRjI GdYGeI (B- (3GdehUd (B(485) s
Keywords: (3GdMQha h GdChaGbs